Portrayal of Grieving in Ali Benjamin’s The Thing About Jellyfish (2015) - Muhamad Luthfi Jayalaksana (Passage, 2019)
Notions about death and grieving have been part of human life for as long as humans have lived. They can be found in many forms such as art, music and literature including children’s literature. The Thing About Jellyfish (2015), a novel for children which is written by Ali Benjamin, tells about a grieving child who is in the transitional phase of being a child to become a teenager. This research attempts to discover the portrayal of grieving experienced by the child main character in the novel. As a study of text, this research uses qualitative method and it employs Kübler-Ross and Kessler theory of five stages of grief (2014) for analysis and Schroth’s theoretical framework in analyzing portrayal of death, dying and grieving in children’s literature (2017) to support the discussion. The findings reveal that grieving is portrayed through the construction of five stages of grief which may be unintentionally employed by the author. From the stages, it is revealed that grieving is also portrayed as a difficult and painful process for the child main character which ends with acceptance and the importance of moving on from grief. Keywords: children’s literature, death, grieving, grieving children, portrayal